Experimental response of additively manufactured metallic pentamode materials confined between stiffening plates. (10th May 2016) - Amendola, A.; Smith, C.J.; Goodall, R.; Auricchio, F.; Feo, L.; Benzoni, G.; Fraternali, F.
Abstract: An experimental investigation on the mechanical response of confined pentamode lattices in the elastic and post-yield regimes is presented. An Electron Beam Melting facility is employed to additively manufacture pentamode lattices confined by terminal plates in a titanium alloy. The given experimental results show that the geometry of the microstructure, and the macroscopic aspect ratio of the confined lattices strongly influence the lateral and vertical stiffness properties of the structure. The post-elastic response of the analyzed materials features acceptable energy dissipation capacity. The presented results highlight several analogies between the mechanical response of confined pentamode lattices and that of elastomeric bearings formed by soft rubber pads and stiffening steel or fiber-reinforced composite layers. They pave the way to future studies on the use of pentamode materials for the fabrication of innovative seismic isolation devices and/or shear-wave band gap systems.